Bisnis Tradisional Masyarakat Badui Luar (Sebuah Jelajah Studi Analisis Akuntansi dan Keuangan Modern) - Sumatirta, Edi; Wulandari, Sisca; Rasydy, La Ode Akbar; Triyanto, Irfan Rusydi; Sabrina, Anida Adelia (Universitas Muhammadiyah Tangerang, 2024)
The Badui people live in seclusion at the foot of Mount Kendeng, Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province. Even though they live without electric lighting, paved roads, and formal education, they feel calm and happy. They fulfill their own welfare, especially by cultivating rice in the fields. The Outer Badui community is more open after interacting with the outside community a lot. Finance and business have become commonplace, whereas previously it was taboo (Sunda Badui language : teu wasa). The front room of the Outer Badui community's house is a traditional production market. Researcher identifies their business activities from a modern accounting and finance perspective. This type of research is qualitative. Researcher conducted a literature study and structured interviews. This research is intended to determine the business management of the Badui community from the perspective of modern accounting and finance. The results of the study show that the Outer Badui community includes taboos on writing (note taking) and reading. Even so, the principles of accounting and finance in doing business, such as grouping data and presenting data, turned out to be what they used to do, but based on memory and orally.